2016
DOI: 10.1007/s13105-016-0471-y
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-9 regulates cardiac fibrosis by targeting PDGFR-β in rats

Abstract: The proliferation of cardiac fibroblasts (CFs) and excessive deposition of extracellular matrix (ECM) are the main pathological characteristics of cardiac fibrosis. In recent years, microRNAs (miRNAs) have been found to be a new kind of regulator in cardiac fibrosis. The purpose of this study was to investigate the role of microRNA-9 (miR-9) in the process of cardiac fibrosis and its mechanism. Treatment of cultured neonatal rat CFs with PDGF-BB or serum suppressed the expression of miR-9. Overexpression of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Moreover, miR-9 plays a role in the treatment of cardiac fibrosis. It has been found that miR-9 regulates cardiac fibroblast proliferation and collagen production (32). The present study found that transfection of miR-9 led to an inhibition of cell proliferation in human HSCs (LX-2) as compared to that noted in the control cells.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, miR-9 plays a role in the treatment of cardiac fibrosis. It has been found that miR-9 regulates cardiac fibroblast proliferation and collagen production (32). The present study found that transfection of miR-9 led to an inhibition of cell proliferation in human HSCs (LX-2) as compared to that noted in the control cells.…”
Section: Discussionsupporting
confidence: 47%
“…PDGF growth factors significantly stimulate cardiac fibroblast proliferation in vitro, and neutralization of PDGF receptors alpha and beta reduces collagen deposition in the myocardium in vivo 57 . Additionally, overexpression of PDGFRβ in cardiac fibroblasts leads to enhanced proliferation and collagen synthesis 58,59 . In addition to downregulation of several downstream signaling molecules, such as FAK, p38, and ERK, we found that Sprr3 loss resulted in significantly reduced activation of PDGFRβ following stimulation with PDGFBB, although neither the expression of PDGFRβ nor binding of PDGFBB to its receptors were notably different in Sprr3 deficient cells as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In organ fibrosis, miR-9-5p may also act as a negative regulator. For instance, miR-9-5p regulates cardiac fibrosis by targeting PDGFR-β in rats [26]. A recent study has demonstrated that miR-9-5p has a protective role in the fibrogenic transformation of human dermal fibroblasts [27].…”
Section: Discussionmentioning
confidence: 99%